Speech Development of a Person in the Context of Language Space - Kadirova Barno Raimovna (Zien Journals, 2023)
the influence of the communicative space on the speech development of the individual is revealed. The main reason that creates a barrier to understanding the culture of speech among students is the deliberate distortion of the language, the language game, the use of slang, which leads to a closure in social, intellectual, and speech development.
Keywords: speech development; language personality; language space